2000
DOI: 10.1148/radiology.217.3.r00dc36619
|View full text |Cite
|
Sign up to set email alerts
|

Medical Physics: Some Recollections in Diagnostic X-ray Imaging and Therapeutic Radiology

Abstract: Medical physics has changed dramatically since 1895. There was a period of slow evolutionary change during the first 70 years after Roentgen's discovery of x rays. With the advent of the computer, however, both diagnostic and therapeutic radiology have undergone rapid growth and changes. Technologic advances such as computed tomography and magnetic resonance imaging in diagnostic imaging and three-dimensional treatment planning systems, stereotactic radiosurgery, and intensity modulated radiation therapy in ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This method can be performed without the application of heavy sedation, has no effect on the general health of an individual and could be repeated as and when required. 3 Even though in recent years, it has been applied in the orofacial areas, it is still not used routinely in the diagnostic procedure for day-to-day clinical practice. USG could be extraordinarily helpful in recognizing, distinguishing and measuring the on-screen nodes in various jaw lesions including the inflammatory swellings due to dental and skin infections, salivary glands disorders and lymph node reaction due to inflammation or metastasis, cysts and cystic components, neoplasms and the post-operative internal tomography of oral tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method can be performed without the application of heavy sedation, has no effect on the general health of an individual and could be repeated as and when required. 3 Even though in recent years, it has been applied in the orofacial areas, it is still not used routinely in the diagnostic procedure for day-to-day clinical practice. USG could be extraordinarily helpful in recognizing, distinguishing and measuring the on-screen nodes in various jaw lesions including the inflammatory swellings due to dental and skin infections, salivary glands disorders and lymph node reaction due to inflammation or metastasis, cysts and cystic components, neoplasms and the post-operative internal tomography of oral tissues.…”
Section: Introductionmentioning
confidence: 99%
“…USG could be extraordinarily helpful in recognizing, distinguishing and measuring the on-screen nodes in various jaw lesions including the inflammatory swellings due to dental and skin infections, salivary glands disorders and lymph node reaction due to inflammation or metastasis, cysts and cystic components, neoplasms and the post-operative internal tomography of oral tissues. 3 It has been observed that in dentistry, the possible application of USG has been discovered and utilized only in very few researches. Hence, a need was felt to conduct a study to determine the potential usefulness of ultrasonography as a complimentary diagnostic tool for odontogenic lesions of the head and neck and to assess the diagnostic capability of ultrasonography the same.…”
Section: Introductionmentioning
confidence: 99%